Ultra-sensitive in situ detection of intracellular Mycobacterium tuberculosis with CRISPR/Cas12a - Lin, Zhiqiang; Song, Zhe; Yu, Hong; Zhou, Yang; Liu, Deliang; Zhang, Peize; Wei, Li; Dai, Guiqin; Liang, Guangyan; He, Zhuojun; Hu, Xiaorong; Chen, Yuying; et al. (Frontiers in Immunology, 2025)
Mycobacterium tuberculosis (Mtb) invades and survives inside macrophages, evading detection and resisting antibiotic treatment, which results in severe clinical consequences such as fatal respiratory failure and systemic inflammation. Rapid and specific detection of intracellular Mtb is crucial for accurate diagnosis and optimizing treatment strategies. In this study, we developed a one-step CRISPR/Cas12a assay targeting the IS6110 gene for the specific and rapid detection of intracellular Mtb. Upon efficient delivery into RAW264.7 macrophages, the assay enabled direct visualization of Mtb IS6110 nucleic acid, generating detectable fluorescence signals. The diagnostic performance was further validated using bronchoalveolar lavage fluid (BALF) samples from clinical participants, achieving a sensitivity of 94%, which surpassed conventional methods such as culture (67%) and Xpert (78%), while maintaining a specificity of 100%. This CRISPR/Cas12a-based assay offers a highly sensitive, rapid, and innovative approach for intracellular Mtb detection, with significant potential to enhance tuberculosis diagnostic methodologies and improve clinical outcomes.